Is CO2 an Indoor Pollutant? Direct Effects of Low-to-Moderate CO2 Concentrations on Human Decision-Making Performance. - Satish, Usha; Mendel, Mark J.; Shekhar, Krishnamurthy; Hotchi, Toshifumi; Sullivan, Douglas; Streufert, Siegfried; Fisk, William J. (Environmental Health Perspectives, 2012)
BACKGROUND: Associations of higher indoor carbon dioxide (CO[sub 2]) concentrations with impaired work performance, increased health symptoms, and poorer perceived air quality have been attributed to correlation of indoor CO[sub 2] with concentrations of other indoor air pollutants that are also influenced by rates of outdoor-air ventilation. OBJECTIVES: We assessed direct effects of increased CO[sub 2], within the range of indoor concentrations, on decision making. METHODS: Twenty-two participants were exposed to CO[sub 2] at 600, 1,000, and 2,500 ppm in an office-like chamber, in six groups. Each group was exposed to these conditions in three 2.5-hr sessions, all on 1 day, with exposure order balanced across groups. At 600 ppm, CO[sub 2] came from outdoor air and participants' respiration. Higher concentrations were achieved by injecting ultrapure CO[sub 2]. Ventilation rate and temperature were constant. Under each condition, participants completed a computer-based test of decision-making performance as well as questionnaires on health symptoms and perceived air quality. Participants and the person administering the decision-making test were blinded to CO[sub 2] level. Data were analyzed with analysis of variance models. RESULTS: Relative to 600 ppm, at 1,000 ppm CO[sub 2], moderate and statistically significant decrements occurred in six of nine scales of decision-making performance. At 2,500 ppm, large and statistically significant reductions occurred in seven scales of decision-making performance (raw score ratios, 0.06 -- 0.56), but performance on the focused activity scale increased. CONCLUSIONS: Direct adverse effects of CO[sub 2] on human performance may be economically important and may limit energy-saving reductions in outdoor air ventilation per person in buildings. Confirmation of these findings is needed.